Lipase-Catalyzed Acidolysis of Egg-Yolk Phosphatidylcholine with Citronellic Acid. New Insight into Synthesis of Isoprenoid-Phospholipids - Magdalena Rychlicka; Natalia Niezgoda; Anna Gliszczyńska (Molecules, 2018)
The development of a biotechnological method for the production of new biologically active phosphatidylcholine containing monoterpene citronellic acid (CA) was the aim of this work. Incorporation of citronellic acid (CA) into egg-yolk phosphatidylcholine (PC) in the lipase-catalyzed acidolysis process was studied. Isoprenoid acid CA was used as an acyl donor and five commercially available immobilized lipases were examined as biocatalysts. The effects of organic solvent, enzyme load, reaction time and molar ratio of substrates on the incorporation of citronellic acid (CA) into the phospholipids were evaluated. Modified phospholipid fraction enriched with CA in the sn-1 position (39% of incorporation) was obtained in high 33% yield using Novozym 435 as biocatalyst. In this study a biotechnological method for production of new phospholipid biopreparation enriched with citronellic acid, which can play an important role as a nutraceutical, was applied.